Iron Deficiency and Iron Deficiency Anemia in Women: A Review - Rao, T. Rama; Teja, D.; Jesintha, D.; Sangeetha, K. (Asian Journal of Pharmaceutical Research and Development, 2025)
Iron deficiency (ID) affects more than 20% of women during their reproductive years, making it the most prevalent micronutrient deficiency in the world. Hepcidin is a peptide hormone that is mostly made by the liver and regulates iron absorption. For ID and iron deficiency anemia (IDA) to be successfully treated with oral preparations, parenteral iron, or blood transfusions, an understanding of iron metabolism is essential. Oral preparations can cause gastrointestinal adverse effects and have varying iron contents. When there are problems with oral iron compliance or tolerance, comorbidities that could impair absorption, or persistent iron losses that surpass absorptive capability, parenteral iron is recommended. When quick iron replenishment is necessary to avoid physiological decompensation, or when administered prior to non-deferrable surgery, it might also be the best choice. In our role as gynecologists, we address women’s heavy menstrual bleeding (HMB) and presume that primary care physicians are attending to the related ID/IDA. It is now our responsibility to take the lead in concurrently diagnosing, treating, and controlling ID/IDA and HMB. This dual management will greatly enhance their standard of living. We will provide a summary of the role iron plays in cellular processes, explain how to diagnose ID/IDA, and assist doctors in selecting from a variety of therapy options in this review.